Ulnar ostectomy decreases the stability of canine cadaver carpi as assessed with stress radiography. Issue 1 (21st September 2018) - Young, Aisha N.; Amsellem, Pierre; Muirhead, Tammy L.; Pack, LeeAnn; Matthews, Andrea R.
Abstract: Distal ulnar ostectomy may be performed palliatively in patients with distal ulnar osteosarcoma. Concurrent arthrodesis of the carpus has been proposed to counteract joint instability following transection of carpal ligaments associated with removal of the distal ulna. The objective of this prospective one group pretest, posttest study was to assess stability of the carpus following distal ulnar ostectomy using pre‐ and postoperative stress radiographic views in a group of canine cadaver limbs. Seven thoracic limbs from six canine cadavers weighing more than 20 kg were obtained. Lateral and dorsopalmar, extended lateral, medial stress, and lateral stress radiographs were made before and after distal ulnar ostectomy. Presurgical canine cadaver carpal angle measurements were as follows (mean ± standard deviation): extension 205.9° ± 5.4; medial stress 25.1° ± 5.7; and lateral stress 13.3° ± 5.2°. Cadaver limb joint angles exceeded those previously reported in live dogs. A significant increase in carpal angle was noted following ulnar ostectomy. The mean increases in carpal angle were as follows: (mean ± standard deviation (95% confidence interval)): extension 6.2° ± 4.9 (2.6–9.8) ( P  = 0.007); medial stress 3.2° ± 3.0 (1.0–5.5) ( P  = 0.015); lateral stress 6.2° ± 5.2 (2.4–10.1) ( P  = 0.010). Findings from this cadaver study support the use of supplementary stabilization for clinical patients undergoing distal ulnar ostectomy. Future studies are needed in clinical patients to evaluate changes in limb positioning and gait associated with distal ulnar ostectomy.